Basic electrical and electronics engineering - Premkumar, N (Anuradha Publications, 2012)
The significance of this book is to provide a basic knowledge in electrical electronics engineering. Electrical engineering deals with DC circuits, AC circuits, electrical measurements, DC generators, DC motors, transformers and single phase induction motors. Electronics engineering covers with electron devices and its applications, digital electronics and communication systems. Each chapter contains solved problems and two mark questions and answers to get complete knowledge of the subject.